THE DEVELOPMENT OF LAB KIT BASED ON POGIL TO TRAIN SCIENCE PROCESS SKILL IN ACID BASE MAIN SUBJECT FOR STUDENTS OF CLASS XI SMAN 1 GURAH KEDIRI (Universitas Negeri Surabaya, 2017)
The study was aimed to know the feasibility of lab kit practical based on POGIL on acid-base material class XI. The feasibility of the lab kit medium based on validity, practicality, and effectiveness aspects. This type of research used development refers to methods of Research and Development (R & D) model that limited to main field testing. This research was a quantitative method with the design of One Group Pretest Posttest Design. The objective of the researched students of grade XI-MIA1 SMAN 1 Gurah Kediri. The data sources of this research shown from validation sheet, student questionnaire response, pretest and posttest science process skills sheet which has been filled by 12 students. The study conducted twice. Kit feasibility based on aspects validity content and construct with an average percentage 85.40% include very appropriate category. Kit feasibility based on practical aspects in terms of students responses obtained percentage with an average of 97.72% include very practical criteria. Kit feasibility based on aspects of effectiveness obtained from the pretest and posttest students science process skills with classical completeness of 91.60% with very effective criteria. It can be concluded that the lab kit on acid-base main subject was feasible based on aspects of validity, practicality, and effectiveness. Keywords: lab kit, validity, practicality, effectiveness